2014
DOI: 10.1098/rspb.2014.1742
|View full text |Cite
|
Sign up to set email alerts
|

Road networks predict human influence on Amazonian bird communities

Abstract: Road building can lead to significant deleterious impacts on biodiversity, varying from direct road-kill mortality and direct habitat loss associated with road construction, to more subtle indirect impacts from edge effects and fragmentation. However, little work has been done to evaluate the specific effects of road networks and biodiversity loss beyond the more generalized effects of habitat loss. Here, we compared forest bird species richness and composition in the municipalities of Santarém and Belterra in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 69 publications
1
23
0
2
Order By: Relevance
“…Furthermore, the recent return to increasing deforestation rates seems likely to continue as a newly appointed administration led by President Jair Bolsonaro (inaugurated 1 January 2019) threatens to expand mining, pasture, and agricultural activities in the Amazon (Artaxo, 2019;Escobar, 2018). Amazon road networks are also anticipated to continue expanding (Ahmed, Ewers, & Smith, 2013;Ahmed et al, 2014;Ahmed, Souza, Riberio, & Ewers, 2013;Laurance et al, 2014). A recent analysis across the entire Brazilian Amazon found that, on average, nearly 17,000 km of roads were added every year between 2004 and 2007 (Ahmed, Souza, et al, 2013).…”
Section: Con Clus Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the recent return to increasing deforestation rates seems likely to continue as a newly appointed administration led by President Jair Bolsonaro (inaugurated 1 January 2019) threatens to expand mining, pasture, and agricultural activities in the Amazon (Artaxo, 2019;Escobar, 2018). Amazon road networks are also anticipated to continue expanding (Ahmed, Ewers, & Smith, 2013;Ahmed et al, 2014;Ahmed, Souza, Riberio, & Ewers, 2013;Laurance et al, 2014). A recent analysis across the entire Brazilian Amazon found that, on average, nearly 17,000 km of roads were added every year between 2004 and 2007 (Ahmed, Souza, et al, 2013).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…For Amazonian birds, a considerable body of research has shown the toll that deforestation (including partial deforestation characterized by forest fragments) and existing roads take on the forest bird community (e.g., Ahmed et al, ; Develey & Stouffer, ; Ferraz et al, ; Laurance, ; Laurance, Stouffer, & Laurance, ; Lees & Peres, , ; Mahood, Lees, & Peres, ; Stouffer, Johnson, Bierregaard, & Lovejoy, ). However, little attention has focused on these deforested landscapes and how ecological succession alters avian communities following anthropogenic change.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, road networks fragment and deteriorate natural habitats (Ahmed et al . ), imposing a filter on animal movement (Kramer‐Schadt et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution, i.e. the extent and density, of road networks can be used to model human influences on tropical forests at larger scales (Mertens et al, 2001;Arima et al, 2008;Bell et al, 2012;Ahmed et al, 2013bAhmed et al, , 2013aAhmed et al, , 2014. It also served as an important input to define the intactness of forest landscapes (Potapov et al, 2008) and the identification of priority road-free areas at a global scale .…”
Section: Characterizing the Spatial Distribution And Coverage Of Loggmentioning
confidence: 99%